ANALISIS KESULITAN MENULIS TEGAK BERSAMBUNG PADA SISWA KELAS V MADRASAH IBTIDAIYAH NEGERI - S. Santoso (INOPENDAS: Jurnal Ilmiah Kependidikan, 2022)
The purpose of this study was to describe (1) the causes of difficulty in cursive writing in fifth grade students at MIN 1 Rembang; (2) the teacher's efforts to help the difficulty of cursive writing in fifth grade students at MIN 1 Rembang. This research is a descriptive qualitative type. Data collection techniques in this study used the interview, observation and documentation methods. The subjects of this study were fifth grade students at MIN 1 Rembang. Key research results that First, the causes of difficulty in cursive writing in fifth grade students at MIN 1 Rembang in the 2021/2022 academic year, including (1) cursive writing control control, (2) slow writing in cursive, (3) how to write does not follow the flow the right line. Second, the teacher's efforts in dealing with the difficulties of cursive writing experienced by fifth grade students at MIN 1 Rembang in the 2021/2022 academic year, namely by (a) the teacher providing direct guidance to students who have difficulty writing cursive, (b) the teacher providing an explanation. back for students who do not understand cursive writing, (c) teachers provide regular training so that students' writing skills can improve according to the application of writing, (d) teachers provide opportunities for those who have good skills in cursive writing to explain to their friends who cannot write in cursive, and (e) teachers can change learning strategies to be more creative.